The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2017
DOI: 10.3390/ijms18050975
|View full text |Cite
|
Sign up to set email alerts
|

Decrease of miR-195 Promotes Chondrocytes Proliferation and Maintenance of Chondrogenic Phenotype via Targeting FGF-18 Pathway

Abstract: Slow growth and rapid loss of chondrogenic phenotypes are the major problems affecting chronic cartilage lesions. The role of microRNA-195 (miR-195) and its detailed working mechanism in the fore-mentioned process remains unknown. Fibroblastic growth factor 18 (FGF-18) plays a key role in cartilage homeostasis; whether miR-195 could regulate FGF-18 and its downstream signal pathway in chondrocyte proliferation and maintenance of chondrogenic phenotypes still remains unclear. The present research shows elevated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 73 publications
(79 reference statements)
0
23
0
Order By: Relevance
“…The procedure was carried out as previously described . HOS and 143B cells after different MALAT1, HDAC4, or miR‐140‐5p intervene were seeded in 96‐well plate and incubated for 48 hours.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The procedure was carried out as previously described . HOS and 143B cells after different MALAT1, HDAC4, or miR‐140‐5p intervene were seeded in 96‐well plate and incubated for 48 hours.…”
Section: Methodsmentioning
confidence: 99%
“…The procedure was carried out as previously described. 29 HOS and 143B cells after different MALAT1, HDAC4, or miR-140-5p intervene were seeded in 96-well plate and incubated for 48 hours. The following assays were performed according to the manufacturer's instructions by applying an EDU detection kit (Keygen).…”
Section: -Ethynyl-20-deoxyuridine (Edu) Incorporation Assaymentioning
confidence: 99%
“…In human endothelial cells, hsamiR-505 inhibited FGF18 mRNA and protein levels and inhibited the activity of a luciferase reporter containing the 3′UTR of FGF18 (Yang et al 2014) suggesting that this microRNA interacts directly with FGF18 mRNA. Another miRNA that interacts with the 3′UTR of FGF18 is miR-195 (Wang et al 2017). Whether these miRNAs are involved in reproductive physiology or medicine is just being explored, although miR-505 abundance was found to be downregulated in endometrial carcinoma (Chen et al 2016), a tissue in which increased FGF18 mRNA levels have been observed (see section on 'Gynaecological cancers'.…”
Section: Fgf8 Signalling and Micrornasmentioning
confidence: 99%
“…Immunohistochemical (IHC) staining. The IHC procedure was performed as previously described (31). The LAD tissue specimens were processed as follows: 4% paraformaldehyde fixation, paraffin-embedding, sectioned to 4-µm thickness, deparaffinization, rehydration, hydrogen peroxide incubation, antigen retrieval, blocked in 10% goat serum (Bioworld Technology, Inc., St. Louis Park, MN, USA), primary antibody incubation (anti-HMGA2 and anti-GAPDH) at 4˚C overnight, secondary antibody incubation (goat anti-rabbit IgG H&L; Abcam) at 37˚C for 20 min, streptavidin-horseradish peroxidase complex incubation, diaminobenzidine tetrahydroc hloride (MedChemExpress, Monmouth Junction, NJ, USA) staining, hematoxylin (Amresco, LLC, Solon, OH, USA) and counterstaining.…”
Section: Methodsmentioning
confidence: 99%